Mengimajinasikan Ulang “Yang Sakral”: Anateisme, Pertaruhan, dan Hal-Hal yang Tidak Selesai - Bawono, Haryo Tejo (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2020)
Religion has often been defined as a response to the sacred. However, this also means that religion is considered meaningful if only one has an idea of the sacred. The problem surfaces when religion seems to be dominated with its brutal and savage face. In these tendencies, any criticism addressed to religion or any suggestion for the sake of changing views about religion will never be considered meaningful or taken into account if the believers do not touch the issue of the sacred at all. This article invites its readers to explore and to reimagine the idea of the sacred and at the same time offers different and imaginative perspectives in the light of Richard Kearney’s concept of anatheism. Humans do not need to separate the sacred from the so-called sensus numinis, not only because they can become and move towards the sacred, but because their lives, bodies, minds, and actions are esentially sacred.